LEGAL PROTECTION FOR ILLEGAL INDONESIAN WORKER IN MALAYSIA - Arohmi, Asnu Fayakun (Media of Law and Sharia, 2020)
This research examines the legal protection provided for illegal Indonesian workers in Malaysia and the obstacles to perform it. Malaysia are the largest number compared to another country in Asia in receiving migrant workers from Indonesia. In total there are 73.178 migrant workers. A large number of Indonesian migrant workers is caused by the lack of jobs vacancy in the country, so citizens look for a job abroad. The requirements to become Indonesian migrant workers are not easy, therefore many of them went abroad illegally. Illegal Indonesian workers often get inhuman treatment. Indonesian goverment should protect every citizen, even though they are illegal workers, since they are still Indonesian citizen. This paper is based on normative-empirical legal research with the data obtained from interviews, as well as from secondary sources provided in laws governing these matters, journals or from trusted sites of internet. The results of this study show that: first, the Law No. 18 of 2017 on Protection of Migrant Worker does not differentiate the protection for illegal and legal Indonesian migrant workers. Second, there are two obstacles faced by the Indonesian government: lack of data regarding the illegal Indonesian workers and lack of state budget to handle the protection of illegal Indonesian workers.